Nano‐Sized Quaternary CuGa2In3S8 as an Efficient Photocatalyst for Solar Hydrogen Production. Issue 11 (3rd September 2014) - Kandiel, Tarek A.; Anjum, Dalaver H.; Takanabe, Kazuhiro
Abstract The synthesis of quaternary metal sulfide (QMS) nanocrystals is challenging because of the difficulty to control their stoichiometry and phase structure. Herein, quaternary CuGa2In3S8 photocatalysts with a primary particle size of ≈4 nm are synthesized using a facile hot‐injection method by fine‐tuning the sulfur source injection temperature and aging time. Characterization of the samples reveals that quaternary CuGa2In3S8 nanocrystals exhibit n‐type semiconductor characteristics with a transition band gap of ≈1.8 eV. Their flatband potential is located at −0.56 V versus the standard hydrogen electrode at pH 6.0 and is shifted cathodically by 0.75 V in solutions with pH values greater than 12.0. Under optimized conditions, the 1.0 wt % Ru‐loaded CuGa2In3S8 photocatalyst exhibits a photocatalytic H2 evolution response up to 700 nm and an apparent quantum efficiency of (6.9±0.5) % at 560 nm. These results indicate clearly that QMS nanocrystals have great potential as nano‐photocatalysts for solar H2 production.